Finding talent and establishing the road to excellence in table tennis - The Dutch case - Faber, I.; Damsma, T.; Pionorcid, J. (Talent identification and development in sport. International perspectives, 2021)
One of the quests that often attracts scientists working in different fields is reveaüng the mystery of exceptional human performance (Ericsson, 2006; Rees et al., 2016). How can we explain this special and unique level of ability? And perhaps more importantly, can we predict who will become excellent from an early stage? Curiosity about these questions coupled with a tremendous drive to explain and predict are most noticeable in sporting domains. However, the challenge of understanding exceptional achievement in sport is complex; both high potential (or talent) and the road to excellence are mulüdimensional constructs, changing over time and requiring an individualized approach (Elferink-Gemser,Jordet, Coelho E Silva, & Visscher, 2011; Philips, Davids, Renshaw, & Portus, 2010).